Sensitive and easy screening for circulating tumor cells by flow cytometry - Lopresti, Alexia (JCI Insight, 2019)
Circulating tumor cells (CTCs) provide easy, repeatable, and representative access to information regarding solid tumors. However, their detection remains difficult because of their paucity, their short half-life, and the lack of reliable surface biomarkers. Flow cytometry (FC) is a fast, sensitive, and affordable technique, ideal for rare-cell detection. Adapted to CTC detection (i.e., extremely rare cells), most FC-based techniques require a time-consuming pre-enrichment step, followed by a 2-hour staining procedure, impeding the efficiency of CTC detection. We overcame these caveats and reduced the procedure to less than 1 hour, with minimal manipulation. First, cells were simultaneously fixed, permeabilized, and then stained. Second, using low-speed FC acquisition conditions and 2 discriminators (cell size and pan-cytokeratin expression), we suppressed the pre-enrichment step. Applied to blood from donors with or without known malignant diseases, this protocol ensures a high recovery of the cells of interest independently of their epithelial-mesenchymal plasticity and can predict which samples are derived from cancer donors. This proof-of-concept study lays the bases of a sensitive tool to detect CTCs from a small amount of blood upstream of in-depth analyses.